2001
DOI: 10.1128/aem.67.12.5526-5529.2001
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Combined Water Potential and Temperature Stresses on Cryptosporidium parvum Oocysts

Abstract: Hosts infected with the parasite Cryptosporidium parvum may excrete oocysts on soils in watersheds that supply public drinking water. Environmental stresses decrease the numbers of oocysts after deposition on soils. However, the rates and effects of combined stresses have not been well characterized, especially for the purposes of estimating decrease in numbers. We subjected oocysts to combined stresses of water potential (؊4, ؊12, and ؊33 bars), above-freezing temperatures (4 and 30°C), and a subfreezing temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…For these reasons, K values determined for different soils (9,20,28,30,39) at near saturation present a wide variation with respect to temperature (Fig. 4).…”
Section: Ooycst Survival In Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, K values determined for different soils (9,20,28,30,39) at near saturation present a wide variation with respect to temperature (Fig. 4).…”
Section: Ooycst Survival In Soilsmentioning
confidence: 99%
“…Desiccation is probably lethal to oocysts (26,35). Walker et al (39) reported that decreasing the soil water potential by adjusting NaCl solution linearly increases the rate of population degradation. Nasser et al (28) also found that incubation for 10 days in dry loamy soil at 32°C resulted in a 3-log 10 reduction in oocyst infectivity but that a saturated soil at a similar temperature caused only a 1-log 10 reduction.…”
mentioning
confidence: 99%
“…This rate could be modified with further information about temperature and soil moisture content prior to storm events [Walker et al, 2001]. Hence k di , i = 1, .…”
Section: Parameter Estimation From Experimental Datamentioning
confidence: 99%
“…Desiccation is probably lethal to oocysts. Walker et al (2001) reported that decreasing soil water potential by adjusting NaCl solution linearly increased the rate of population degradation. Nasser et al (2007) also found incubation for 10 days in dry loamy soil at 32 o C resulted in a 3-log 10 reduction in oocyst infectivity, but a saturated soil caused only 1-log 10 reduction at a similar temperature.…”
Section: Effect Of Soil Moisture On Oocyst Survivalmentioning
confidence: 99%